High moisture corn grains silage in substitution of diet dry corn to broilers bred in two systems - Gonçalves, Jane Cristina; Sartori, José Roberto; Pezzato, Antonio Celso; Costa, Ciniro; Martinez, Karina Ludovico de Almeida; da Cruz, Valquíria Cação; Madeira, Luciene Aparecida; Oliveira, Henrique Nunes de (Pesquisa Agropecuaria Brasileira, 2005)
<!–[if gte mso 9]> Normal 0 <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> The aim of this work was to evaluate the inclusion of high moisture corn grains silage, in substitution of dry corn, in diets of broilers bred in conventional and alternative systems. One-day old male Cobb chicks (720) were distributed in randomized blocks, according to a 2x3 factorial consisting of two systems (conventional and alternative), and three levels of silage (0%, 30% and 60%), with four replications per treatment. Means of weight, weight gain, ration consumption, feed conversion, production factor and mortality were obtained in 21, 42 and 49 days old broilers. In the final of the experiment 28 chickens per treatment were used to determine carcass yield, cuts and abdominal fat. The inclusion in diet until 60% of humid grain corn silage, in substitution of dry corn, decreased the ration cost, without affecting performance (in 21, 42 and 49 days old) and carcass yield of broilers (49 days). In alternative breeding system, independently of inclusion level of high moisture corn grains silage, performance was lower, however the economic return was higher.